2016
DOI: 10.1542/peds.2016-0895
|View full text |Cite|
|
Sign up to set email alerts
|

Reasons for Trying E-cigarettes and Risk of Continued Use

Abstract: BACKGROUND: Longitudinal research is needed to identify predictors of continued electronic cigarette (e-cigarette) use among youth. We expected that certain reasons for first trying e-cigarettes would predict continued use over time (eg, good flavors, friends use), whereas other reasons would not predict continued use (eg, curiosity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
108
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 35 publications
17
108
1
3
Order By: Relevance
“…28 A recent study in Ontario's Niagara region found that only 6% of adolescents reported using e-cigarettes for reduction or cessation of smoking, 20 with several studies finding that young smokers are less likely than older smokers to report using e-cigarettes to quit smoking. 13,29,30 Consistent with other studies, use is more prevalent among males; 1,13,14,20 users of other tobacco products such as little cigars, water pipes and smokeless tobacco; 16,31 users of alcohol and marijuana; 10 and students who perceive that access is easy. 13 Use is less prevalent among students who perceive they risk harming themselves by using e-cigarettes.…”
Section: Discussionsupporting
confidence: 78%
“…28 A recent study in Ontario's Niagara region found that only 6% of adolescents reported using e-cigarettes for reduction or cessation of smoking, 20 with several studies finding that young smokers are less likely than older smokers to report using e-cigarettes to quit smoking. 13,29,30 Consistent with other studies, use is more prevalent among males; 1,13,14,20 users of other tobacco products such as little cigars, water pipes and smokeless tobacco; 16,31 users of alcohol and marijuana; 10 and students who perceive that access is easy. 13 Use is less prevalent among students who perceive they risk harming themselves by using e-cigarettes.…”
Section: Discussionsupporting
confidence: 78%
“…A previous study showed that adolescents who first tried to use e-cigarettes because they were cheap, because they wanted nicotine, or because they wanted to quit smoking tended to continue using e-cigarettes [19]. Additionally, adults who tried e-cigarettes for goal-oriented reasons (e.g., to use e-cigarettes where smoking was not allowed or to quit) were more likely to report continued use [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…Smokers who used e-cigarettes for smoking cessation showed a higher smoking cessation rate, whereas those with other reasons showed lower smoking cessation rates than non-e-cigarette users [20]. Some studies have reported predictors of continued e-cigarette use [19] and the reasons for experimentation among adolescents [21]; however, few have investigated the reasons for initiation regarding the intensity of e-cigarette use. This study aims to determine the relation between the frequency of ecigarette use and the frequency and intensity of conventional cigarette smoking among Korean adolescents based on a nationally representative cross-sectional sample.…”
Section: Introductionmentioning
confidence: 99%
“…This is a factor cited by some youth for trying ENDS 19. While some smokers would quit smoking with ENDS, many more would engage in dual use 20.…”
Section: Helping Smokers Quit Versus Triggering Relapse In Former Smomentioning
confidence: 99%